Using the Frailty Assessment for Care Planning Tool (FACT) to screen elderly chronic kidney disease patients for frailty: the nurse experience - Moffatt H (Dove Medical Press, 2018)
Heather Moffatt,1 Paige Moorhouse,1,2 Laurie Mallery,1,2 David Landry,1 Karthik Tennankore2 1Nova Scotia Health Authority, Halifax, NS, Canada; 2Dalhousie University, Halifax, NS, CanadaPurpose: Recent evidence supports the prognostic significance of frailty for functional decline and poor health outcomes in patients with chronic kidney disease. Yet, despite the development of clinical tools to screen for frailty, little is known about the experiential impact of screening for frailty in this setting. The Frailty Assessment for Care Planning Tool (FACT) evaluates frailty across 4 domains: mobility, function, social circumstances, and cognition. The purpose of this qualitative study was as follows: 1) explore the nurse experience of screening for frailty using the FACT tool in a specialized outpatient renal clinic; 2) determine how, if at all, provider perceptions of frailty changed after implementation of the frailty screening tool; and 3) determine the perceived factors that influence uptake and administration of the FACT screening tool in a specialized clinical setting.Methods: A semi-structured interview of 5 nurses from the Nova Scotia Health Authority, Central Zone Renal Clinic was conducted. A grounded theory approach was used to generate thematic categories and analysis models.Results: Four primary themes emerged in the data analysis: “we were skeptical”, “we made it work”, “we learned how”, and “we understand”. As the renal nurses gained a sense of confidence in their ability to implement the FACT tool, initial barriers to implementation were attenuated. Implementation factors – such as realistic goals, clear guidelines, and ongoing training – were important factors for successful uptake of the frailty screening initiative.Conclusion: Nurse participants reported an overall positive experience using the FACT method to screen for frailty and indicated that their understanding of the multiple dimensions and subtleties of “frailty” were enhanced. Future nurse-led FACT screening initiatives should incorporate those factors identified as being integral to program success: realistic goals, clear guidelines, and ongoing training. Adopting the evaluation of frailty as a priority within clinical departments will encourage sustainability.Keywords: frailty, screening, feasibility, qualitative, end stage renal disease, decision making